A History of Chinese Buddhist Faith and Life - Shengkai (Studies on East Asian Religions Ser., 2020)
This book is a study of the formation and the practice of Buddhist canons and an attempt to present as fully as possible the panorama of Chinese Buddhist faith. The book uses textual and archaeological sources, including Dunhuang texts, and adopts multiple perspectives such as textual evidence, historical circumstances, social life, as well as the intellectual background at the time.